Prophylactic colectomy and rectal preservation in FAP: systematic endoscopic follow-up and adenoma destruction changes natural history of polyposis - Pasquer, Arnaud; Benech, Nicolas; Pioche, Mathieu; Breton, Antoine; Rivory, Jerome; Vinet, Olivier; Poncet, Gilles; Saurin, Jean Christophe (Endoscopy International Open, 2021)
Background and study aims Prophylactic surgery of familial adenomatous polyposis (FAP) includes total colectomy with ileorectal anastomosis (IRA) to proctocolectomy with ileoanal anastomosis (IAA). Surgical guidelines rely on studies without systematic endoscopic follow-up and treatment. Our aim was to report our experience based on a different approach: therapeutic follow-up, comparing in this setting IRA and IAA in terms of oncological safety and quality of life.Patients and methods Between January 1965 and November 2015, all patients who underwent prophylactic surgery for FAP with therapeutic endoscopic follow-up in Lyon University hospital: systematic endoscopic treatment of adenomas, were retrospectively and prospectively (since 2011) included.Results A total of 296 patients were analyzed: 92 had proctocolectomy with IAA (31.1 %), 197 total colectomy with IRA (66.5 %), and seven abdominoperineal resections (2.4 %). Median follow-up was 17.1 years (range, 0–38.1). Incidence of secondary cancer (IR vs. IAA) was 6.1 % vs. 1.1 % (P = 0.06; 95 %CI 0.001–0.36). The 15-year cancer-free and overall survival (IR vs. IAA) were 99.5 % vs 100 % (P = 0.09) and 98.9 % vs. 98.8 % (P = 0.82), respectively. Postoperative morbidity occurred in 44 patients: 29 (14.7 %) in the IRA and 15 (16.3 %) in the IAA group (P = 0.72). The mean number of stools per day in the respective groups were 4.4 (2.5) vs. 5.5 (2.6) (P = 0.001). Fecal incontinence occurred in 14 patients (7.1 %) in the IRA vs. 16 (17.4 %) in the IAA group (P = 0.03).Conclusions A combination of therapeutic endoscopic treatment and extended rectal preservation appears to be a safe alternative to ileoanal J-pouch anastomosis.